Adrenaline is effective in reversing the inadequate heart rate response in atropine treated organophosphorus and carbamate poisoning. (3rd July 2021) - Samprathi, Abhishek; Chacko, Binila; D'sa, Shilpa Reynal; Rebekah, Grace; Vignesh Kumar, C.; Sadiq, Mohammad; Victor, Punitha; Prasad, John; Jayakaran, Jonathan Arul Jeevan; Peter, John Victor
Abstract: Background: In acute organophosphorus (OP) or carbamate poisoning, some patients require high dose atropine to counteract the effects on heart rate (HR) and blood pressure (BP). This study describes the factors associated with high dose atropine therapy and the use of adrenaline to reverse the inadequate HR response to atropine. Methods: Consecutive patients admitted to the intensive care unit (ICU) were prospectively recruited. Demographic data, treatment and outcomes of patients who failed to achieve target HR (100/min) or systolic BP >90 mm Hg with either a cumulative atropine dose of 100-mg within 6-h following admission or an infusion of 30 mg/h for at least 3-h were compared with patients who achieved the targets. Factors associated with high dose atropine therapy were explored using logistic regression analysis and expressed as odds ratio (OR) with 95% confidence intervals (CIs). Results: Of the 181 patients admitted with OP or carbamate poisoning, 155 patients fulfilled inclusion criteria. The mean (SD) age was 35.7 (15.8) years; admission APACHE-II score was 14.6 (7.5). Heart rate and/or BP target was not achieved in 13.6%. In these patients, target HR was achieved after adding adrenaline infusion at 2–4 μg/min. Ventilation duration (11.6 ± 6.3 vs. 8.4 ± 6.9 days, p  = 0.05) and ICU stay (12.3 ± 5.8 vs. 8.9 ± 5.8 days, p  = 0.01) were longer in patients requiring high dose atropine when compared with others. On multivariate logistic regression analysis, shorter time to presentation to hospital ( p  = 0.04) was associated with need for high dose atropine. Overall mortality was 9% and similar in both groups ( p  = 0.41). Conclusions: High dose atropine therapy is required in a subset of patients with OP and carbamate poisoning and was associated with longer ventilation duration and ICU stay. Adrenaline infusion improved hemodynamics in these patients.